Online third-order liquid chromatographic data with native and photoinduced fluorescence detection for the quantitation of organic pollutants in environmental water - Pellegrino Vidal, Rocío Belén (2018)
Fil: Fil: Pellegrino Vidal, Rocío Belén. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR-CONICET); Argentina.